Digital Survey as a Method for Creative Thinking in Architectural Design (EAAE Annual Conference Proceedings, 2023)
Architectural surveying has always been the purview of the architect, despite the fact that it is practiced by other disciplines. Technological innovations in surveying have led, at least in France, to an ambivalent relationship with these new methods of documenting the existing. Although very rare in teaching, learning digital surveying techniques is nevertheless inevitable for future architects who will be required to handle these tools directly or to interact closely with their operators.